Growth and nitrogen uptake modeling in composite and hybrid corn varieties - Fajar Ilhamy, Muhammad Rizki; Suwarto; Herdhata Agusta; Abdul Qadir (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Corn is a strategic commodity in Indonesia's agricultural and economic development. The problem of corn production can be overcome with proper usage of nitrogen fertilization. Dynamic modeling can be used as a tool to solve this problem. This study aimed to develop a dynamic model for the growth and nitrogen uptake of composite and hybrid corn varieties. Stages in the model construction: (1) identifying system components, (2) model construction, (3) simulation, and (4) validation. The growth model is a construction of the plant's ecophysiological response to solar radiation and temperature in photosynthesis. A growth model in composite and hybrid corn varieties with simulated dry weight as output has been constructed validly. The model input components, such as light use efficiency, extinction coefficient, specific leaf area, and carbohydrate partition coefficient varied at each development phase for each variance. The actual total dry weight on the Pioneer 27 variety was 6,406 kg ha-1 with a simulated total dry weight was 6,228 kg ha-1, and the actual total dry weight on the Bisma variety was 5,127 kg ha-1 with a simulated total dry weight was 4,864 kg ha-1. The level of validity of the Pioneer 27 variety growth model reached 83.5% and the Bisma variety reached 80%. Keywords: Bisma; dry weight; growth model; nitrogen uptake; Pioneer 27; simulation; validation